2016
DOI: 10.1134/s1063772916040041
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of the Universe at different cosmological epochs

Abstract: A step-by-step foundation for the differential character of the Universe's rotation is presented. First, invoking the concept of spacetime foam with spin, it is reasonable to assume that the very early Universe can be described by the Dirac equation. Second, it is shown using the Ehrenfest theorem that, from a classical point of view, the early Universe can be described by the Papapetrou equations. Third, it is stressed that our Universe can perform only rotational motion. It is shown based on the spin part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Although the asymmetry can be the results of a measurement error, it is difficult to identify reasons for such differences due to errors in SDSS pipeline, as both clockwise and anti-clockwise galaxies were measured in the same parts of the sky, and were separated into two classes only after the images and photometric measurements were acquired. The differences observed in this study can also be explained by a violation of the cosmological principle (Longo 2011;Shamir 2012;Horsch 2013;Güllü and Tekin 2014;Tasseten and Tekin 2016;Chechin 2016), as the differences in asymmetry in different directions of observation might indicate that the local universe is not isotropic. While several observations have shown structures that violate the homogeneity assumption of the cosmological principle (Balázs et al 2015), the observation reported here provides preliminary evidence for the violation also of the isotropy assumption.…”
Section: Colourmentioning
confidence: 61%
“…Although the asymmetry can be the results of a measurement error, it is difficult to identify reasons for such differences due to errors in SDSS pipeline, as both clockwise and anti-clockwise galaxies were measured in the same parts of the sky, and were separated into two classes only after the images and photometric measurements were acquired. The differences observed in this study can also be explained by a violation of the cosmological principle (Longo 2011;Shamir 2012;Horsch 2013;Güllü and Tekin 2014;Tasseten and Tekin 2016;Chechin 2016), as the differences in asymmetry in different directions of observation might indicate that the local universe is not isotropic. While several observations have shown structures that violate the homogeneity assumption of the cosmological principle (Balázs et al 2015), the observation reported here provides preliminary evidence for the violation also of the isotropy assumption.…”
Section: Colourmentioning
confidence: 61%
“…8) It may be noted that, many cosmologists are working on 'cosmic rotation' . According to Fani Dosopoulou et al [11]: "Current observations are consistent with small amounts of universal rotation, which means that, if the universe rotates, it does so very slowly. This is also in agreement with the inflationary scenario, where the exponential expansion is expected to essentially eliminate any traces of primordial vorticity.…”
Section: Discussion On the Proposed Assumptions And Their Consequencementioning
confidence: 79%
“…We would like to appeal that, rotation is a natural phenomena for most of the sub-universal objects like galaxies, stars and planets and current gigantic universe can also be imagined to be an evolving and rotating sphere. Over the last sixty plus years, numerous rotating and expanding general relativitycompatible cosmological models have been developed [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. L.M.…”
Section: Cosmic Rotationmentioning
confidence: 99%